MARKETING STRATEGY AND PROMOTION OF INTEREST IN LEARNING DRIVING USING CANVAS MODEL BUSINESS APPROACH METHOD (CASE STUDY OF PRATAMA JAYA DRIVING SCHOOL IN DEPOK) - Prihatin Budi Susanto; Rita Puspita Sari; Bernandus Yoseph Beda; Agus Arifin; Reimond Hasangapan Mikkael (SEAN Institute, 2023)
Pratama Jaya driving school is a company in the field of driving course services in Depok City, West Java. The customer segmentation targeted by the Pratama Jaya Driving School includes students and employees in Depok City who do not yet have the ability to drive but have the intention to learn to drive. Research objective: evaluate the form of the Pratama Jaya driving school business by collecting the required data such as the existing business model, internal analysis data such as customer profiles by interviewing the company owner and data analysis using literature studies. This research uses the Business Model Canvas which is a method for developing a business by giving an overall picture form represented by nine blocks. Methods: using a questionnaire distributed by the community including students and employees over the age of 17 in the city of Depok with indicators made for the required data requirements. Results: From the SWOT analysis, the Business Model Canvas is obtained as a consideration for the proposed strategy. Conclusion: the Canvas business model is suitable to be applied to the Pratama Jaya driving school.